Odpowiedzi

2009-12-15T20:04:09+01:00
2009-12-15T20:06:28+01:00
A) 3x+y=5
2x-y=0
+ -----------
5x=5/:5
x=1
x=1
2*1-y=0
x=1
-y=-2/:(-1)
x=1
y=2
b)2x-y=5
x+y=4
+ --------
3x=9/ :3
x=3
x=3
3+y=4
x=3
y=1
c) -x-y=-6
-x+y=2
+ ------------
-2x=4/:(-2)
x=-2
x=-2
-(-2)+y=2
x=2
y=-2
d)4x-5y=-4
-2x+3y=1,1/*2
4x-5y=-4
-4x+6y=2,2
+ ---------------
y= -1,8
4x-5(-1,8)=-4
y= -1,8
4x=-4-9
y=-1,8
4x=-13/:4
y= -1,8
x=-3,25
y=-1,8
Najlepsza Odpowiedź!
2009-12-15T20:09:38+01:00
A)3x+y=5 /*2 →→→→→→→ 3x+2=5
2x-y=0 /*-3 3x=5-2
6x+2y=10 3x=3 /:3
-6+3y=0 x=1

6x i -6x się skrócą więc zostanie:
5y=10 /:5
y=2

Odp.X jest równe 1, a y 2.

b)2x-y=5 →→→→→→→ 2x-1=5
x+y=4 /*-2 2x=6 /:2
2x-y=5 x=3
-2x-2y=-8
-3y=-3 /:-3
y=1


c)-x-y=-6 →→→→→→→ -2-y=-6
-x+y=2 -y=-4 /*-1
-2x=-4 /:-2 y=4
x=2

d) 4x-5y=-4 →→→→→→→ 4x-5*-1,8=-4
-2x+3y=1,1 /*2 4x=-4-9
4x-5y=-4 4x=-13 /:4
-4x+6y=2,2 x=-3,25
y=-1,8

Proszę ;p
1 5 1